PERTANGGUNG JAWABAN PIDANA TERHADAP PELAKU TINDAK PIDANA PERDAGANGAN ORANG - Siti Rochmah; Frans Simangunsong (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2023)
The act but requesting, accommodating, bringing, transferring, or accepting someone out of fear of violence with the intention of exploiting or encouraging their exploitation is a cybercrime known as the human trafficking. Criminal acts of human trafficking are increasing every year, so that it becomes a serious problem that needs to be handled by Indonesian law enforcement. The goal of this study is to find out the responsibility of individuals who engage in trafficked in humans in violation of the law terms of the Law of the Republic of Indonesia Number 21 of 2007 and to find out how the sentence is imposed on individuals who commit these crimes. human trafficking from the perspective of the Law of the Republic of Indonesia. The research process used to make this journal includes normative juridical research, namely research on secondary literature data or materials that have been collected, described in a narrative style, then examined qualitatively. Criminal responsibility relates the grounds for imposing criminal sanctions to the burden of responsibility imposed on the person who committed the crime. Law Number 21 of 2007 concerning human trafficking regulates criminal sanctions to those who violate acts of human trafficking. The maximum and minimum limits give judges the ability to impose criminal sanctions on those involved in human trafficking. Criminal Law no. 21 of 2007 was the beginning of the criminal mismatch